Heuristic Reasoning and Conversational Cases in the Gospel of John - Yonas Prasetya; Edward Sitepu; Milisi Sembiring (P3TK, Sanata Dharma University, 2022)
The grace of Christ needs to be on the agenda of preaching in the Gospels, especially in the Gospel of John. In the current pandemic atmosphere, heuristic reasoning can be grounded from the Gospel of John. The counselee needs clarity about himself and why he must entrust his life to the Lord Jesus. And the contribution of Christianity is to strive for them to grow in faith and become mature disciples of Christ in the future. The process of becoming a disciple of Christ of course by paying attention to the cognitive workings of the individual concerned. And it becomes an important part of Christian ministry so that the quality of the faith that is reached is visible and useful in his life. Heuristic reasoning can be one of the proposed models because Christ himself used this reasoning with many people, including His disciples.